Wiley practitioner's guide to GAAS 2013 : covering all SASs, SSAEs, SSARSs, and interpretations - Flood, Joanne M. (Wiley, 2013)
BThe clearest, easiest-to-use guide to understanding GAAS 2013 on the market'fullyupdated/b This latest resource to understanding GAAS addresses the toughest part of thejob'identifying, interpreting, and applying the many audit, attest, review, and compilationstandards relevant to a particular engagement. The only GAAS reference organized according topractitioners' actual use of the Statements on Auditing Standards (SASs), inside you'll findexamples and illustrations for testing internal controls, techniques for remaining compliantwith each standard, and explanations of the reasons for each pronounceument.ulliA brief identification of each SAS, SSae, and SSARS, with its effective date and tips onwhen to apply it/liliA convenient and comprehensive glossary of official definitions, which are usuallyscattered throughout a standard/liliBehind-the-scenes explanations of the reasons for each pronouncement and brief explanationsof the basic ideas of the section/liliConcise listing and descriptions of each standard's specific mandate/liliEasy-to-read capsule summary of interpretations, plus selected AICPA practice alerts and advisories/liliHelpful techniques for remaining compliant with each standard/iliExamples and illustrations for testing internal controls/i/ul iWiley Practitioner's Guide to GAAS 2013/i presents each statement individually, explaining howthe standards are related and offering guidance on the entire engagement process in the form ofpractice notes, checklists, questionnaires, and real-world examples that illustrate how thefundamental requirements of each section are applied.